Injectable hydrogels of newly designed brush biopolymers as sustained drug-delivery vehicle for melanoma treatment - Shukla A.; Singh A.P.; Maiti P. (My University, 2025)
Novel biocompatible and brush copolymers have been developed for cancer treatment using its controlled drug-release potential. Polyurethane graft on linear dextrin has been synthesized to control the hydrophilic–hydrophobic balance for regulated drug delivery. The properties of the graft copolymers have been tuned through graft density. The prepared grafts are thermally stable and mechanically strong. An injectable hydrogel has been developed by embedding the drug-loaded brush copolymers in methyl cellulose to better control the release for a prolonged period, importantly by keeping the drug release at a constant rate. Cellular studies indicate the biocompatible nature of the brush copolymers whose controlled and slow release of drug exhibit significant cytotoxic effects on cancer cells. Endocytosis of drug tagged contrast agent indicates greater transport of biologically active material inside cell as observed through cellular uptake studies. In vivo studies on melanoma mice exhibit the real efficacy of the controlled drug release from the injectable hydrogel with significant melanoma suppression without any side effects as opposed to severe toxic effects observed in conventional chemotherapy. Special application method of drug-loaded hydrogel just beneath the tumor makes this system incredibly effective through confinement. Thus, brush copolymer injectable hydrogel is a promising vehicle for control release of drug for cancer treatment in future. © 2021, The Author(s).